PEMASARAN DAN ERA PERKEMBANGANNYA: (STUDI KASUS: KEBOCORAN DATA 91 JUTA AKUN PENGGUNA TOKOPEDIA) - Fauzia, Dara; Rusmanti Fisabililah, Endah; Nirmalawati, Syifa; Cassena, Dewuwuh; Sundari, Asri (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2024)
The business cycle of marketing is closely related to meeting consumer needs. The shift from traditional marketing to the digital era has become a part of companies' strategies to market their products. Through digital marketing, companies can easily market their products online, which consumers can access via social media platforms, websites, marketplaces, and online advertising. This research was conducted using qualitative methods, with data and information selection using the library research method. The sources in this study are secondary data derived from literature reviews of various documents, literature related to the research problem or topic, and existing journals. The findings indicate that the emergence of the digital era has the power to enhance various aspects of people's lives, particularly in meeting their needs. The study's findings show that as technology evolves, new issues will arise in consumer behaviour, market trends, and cyber security. Companies, organisations, and related institutions must be prepared to address these challenges.